2015
DOI: 10.7863/ultra.15.14.10067
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric and Gynecologic Resident Ultrasound Education Project

Abstract: Current ultrasound education in Ob/Gyn varies across Canadian residency programs. Training in Gyn ultrasound is lacking, and both trainees and physicians confirmed the need for a standardized Gyn ultrasound curriculum for residency programs in Canada.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…giving the participants a voice [ 23 ]. The results should, therefore, be valid for all medical staff who use ultrasound as a diagnostic tool [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…giving the participants a voice [ 23 ]. The results should, therefore, be valid for all medical staff who use ultrasound as a diagnostic tool [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies across different specialties have noted a deficiency in their current ultrasound curricula . One study of radiology residents concluded that residents needed at be involved in least 200 ultrasound examinations to be able to develop an acceptable level of competence in ultrasound, emphasizing the importance of experience in clinical practice .…”
Section: Discussionmentioning
confidence: 99%
“…Competency self-assessments are used as a method to identity improvement in clinical skills or professionalism [4,5,10,11]. Although there are some negative views on self-assessment [3,5,14], a real performance level is reflected in self-assessment [4,15] and this method is recommended [2,4,16,17] as it has its own meaning since it is an assessment of the self-perceived ability by the students themselves. Moreover, some argue that accurate self-assessment [10,14] is one of the competencies necessary for physicians in the era of lifelong learning [18].…”
Section: Introductionmentioning
confidence: 99%